A Bispidine Iron(IV)–Oxo Complex in the Entatic State. (28th July 2016) - Comba, Peter; Fukuzumi, Shunichi; Koke, Carsten; Martin, Bodo; Löhr, Anna‐Maria; Straub, Johannes
Abstract: For a series of Fe IV =O complexes with tetra‐ and pentadentate bispidine ligands, the correlation of their redox potentials with reactivity, involving a variety of substrates for alkane hydroxylation (HAT), alkene epoxidation, and phosphine and thioether oxidation (OAT) are reported. The redox potentials span approximately 350 mV and the reaction rates over 8 orders of magnitude. From the experimental data and in comparison with published studies it emerges that electron transfer and the driving force are of major importance, and this is also supported by the DFT‐based computational analysis. The striking difference of reactivity of two isomeric systems with pentadentate bispidines is found to be due to a destabilization of the S= 1 ground state of one of the ferryl isomers, and this is supported by the experimentally determined redox potentials and published stability constants with a series of first‐row transition metal ions with these two isomeric ligands.